2012
DOI: 10.3109/02656736.2011.638963
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity of endothelial cells on synthetic vascular graft material

Abstract: Cells grown on ePTFE were more susceptible to mild hyperthermia-induced death, compared to those on tissue culture dishes. Significant cell death on ePTFE mainly via apoptosis can be achieved by optimising temperature and duration of exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…It has been reported that exposure to heat stress caused apoptosis to occur in endothelial cells (Brinton et al 2012). Additionally, heat stress induced cell apoptosis by activating apoptosis-related genes, such as caspase and bax/bcl-2.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that exposure to heat stress caused apoptosis to occur in endothelial cells (Brinton et al 2012). Additionally, heat stress induced cell apoptosis by activating apoptosis-related genes, such as caspase and bax/bcl-2.…”
Section: Introductionmentioning
confidence: 99%
“…Since HSPs are known to be protective [3941], it is possible, albeit speculated, that the induction of HSPs may be also involved in the inhibitory effect of heat stress on apoptosis in LPS-stimulated PMECs. Interestingly, calpain has been suggested to target and cleave HSPs [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In these preliminary results, the levels of TNF-α, IL-1β and IL-6 varied with the recovery time following heat exposure, and were highest in the HS-6 group. Previous studies have suggested that intense heat stress may induce endothelial cell apoptosis, and that endothelial cells exhibit significant apoptosis during the acute-phase response to heat stress (28,29). A previous study by Gu et al (29) demonstrated that in vitro , the rate of apoptosis in human umbilical vein endothelial cells is associated with time after heat treatment, and apoptosis increased most markedly when human umbilical vein endothelial cells were treated at 43°C for 2 h, followed by replacement with fresh media and further incubation for 6 h. In the present study, the numbers of apoptotic aortic endothelial cells were highest in the HS-6 group.…”
Section: Discussionmentioning
confidence: 99%